2014 IEEE/RSJ International Conference on Intelligent Robots and Systems 2014
DOI: 10.1109/iros.2014.6943205
|View full text |Cite
|
Sign up to set email alerts
|

Long-term topological localisation for service robots in dynamic environments using spectral maps

Abstract: Abstract-This paper presents a new approach for topological localisation of service robots in dynamic indoor environments. In contrast to typical localisation approaches that rely mainly on static parts of the environment, our approach makes explicit use of information about changes by learning and modelling the spatio-temporal dynamics of the environment where the robot is acting. The proposed spatio-temporal world model is able to predict environmental changes in time, allowing the robot to improve its local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 27 publications
0
54
0
1
Order By: Relevance
“…However, these approaches present a decrease in robustness when facing long-term changes [15], as again they are prone to error when features appear and disappear over time. In [3], [4] dynamic models of the topological space that explicitly represent the environment changes and try to identify patterns by means of the Fourier transform are presented, for both localisation (node level) and navigation (transitions between nodes). This ability of pattern identification allows for state prediction, which as shown in [4] can improve navigation performance.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these approaches present a decrease in robustness when facing long-term changes [15], as again they are prone to error when features appear and disappear over time. In [3], [4] dynamic models of the topological space that explicitly represent the environment changes and try to identify patterns by means of the Fourier transform are presented, for both localisation (node level) and navigation (transitions between nodes). This ability of pattern identification allows for state prediction, which as shown in [4] can improve navigation performance.…”
Section: Related Workmentioning
confidence: 99%
“…Previous work has shown that the predictive capabilities of the spectral models improve visual-based mobile robot localisation [3], navigation [4] and planning [5]. However, the previous works were aimed at proof-of-concept verification of the Frequency Map All authors are with the University of Lincoln, UK.…”
Section: Introductionmentioning
confidence: 99%
“…Sünderhauf and Neubert [34,35] mined a dictionary of superpixel-based visual-terms from long-term data and used this dictionary to translate between the appearance of given locations across seasons. Krajnik et al [36] used Fourier analysis to identify the cyclical changes of the environment states and showed that predicting these states for a particular time improves long-term localization [37].…”
Section: Visual Navigation In Changing Environmentsmentioning
confidence: 99%
“…Recently, some authors proposed to exploit these conflicting measurements in order to obtain information about the world dynamics and proposed representations that model the environment dynamics explicitly. These dynamic representations have shown their potential by improving mobile robot localization in changing environments [3], [4], [5], [6].…”
Section: Tkrajnik@lincolnacukmentioning
confidence: 99%